CD4+CD8+ T-Lymphocytes in Xenogeneic and Human Graft-versus-Host Disease - Alhaj Hussen, Kutaiba; Michonneau, David; Biajoux, Vincent; Keita, Seydou; Dubouchet, Laetitia; Nelson, Elisabeth; Setterblad, Niclas; Le Buanec, Helene; Bouaziz, Jean-David; Guimiot, Fabien; Socié, Gérard; Canque, Bruno (Frontiers in Immunology, 2020)
Mechanisms driving acute graft-versus-host disease (aGVHD) onset in patients undergoing allogeneic hematopoietic stem cell transplantation (allo-HSCT) are still poorly understood. To provide a detailed characterization of tissue-infiltrating T lymphocytes (TL) and search for eventual site-specific specificities, we developed a xenogeneic model of aGVHD in immunodeficient mice. Phenotypic characterization of xenoreactive T lymphocytes (TL) in diseased mice disclosed a massive infiltration of GVHD target organs by an original CD4+CD8+ TL subset. Immunophenotypic and transcriptional profiling shows that CD4+CD8+ TL comprise a major PD1+CD62L-/+ transitional memory subset (>60%) characterized by low level expression of cytotoxicity-related transcripts. CD4+CD8+ TL produce high IL-10 and IL-13 levels, and low IL-2 and IFN-, suggestive of regulatory function. In vivo tracking of genetically-labelled CD4+ or CD8+ TL subsequently found that CD4+CD8+ TL mainly originate from chronically activated cytotoxic TL (CTL). On the other hand, phenotypic profiling of CD3+ TL from blood, duodenum or rectal mucosa in a cohort of allo-HSCT patients failed to disclose abnormal expansion of CD4+CD8+ TL independent of aGVHD development. Collectively, our results show that acquisition of surface CD4 by xenoreactive CD8+ CTL is associated with functional diversion toward a regulatory phenotype, but rule out a central role of this subset in the pathogenesis of aGVHD in allo-HSCT patients.